Menjelajah konsep manusia - Sakinah, Nur Imanis (Maliki Interdisciplinary Journal, 2024)
This article explores the concept of humanity within the realm of social sciences, investigating perspectives from various disciplines such as sociology, anthropology, psychology, economics, and politics. Centered on human interaction with their environment, the discussion encompasses the understanding of humanity, its essence as both individual and social beings, and its connection to culture. It is anticipated that this article provides a comprehensive insight into the complexity of humanity and its role in societal dynamics.